The study of quantitative traits with different statistical parameters in registered inbred rice (Oryza sativa L.) - Cantila, Aldrin Y.; Abdula, Sailila E.; Candalia, Haziel Jane C. (2017)
The primary quantitative trait grain yield (GY) and secondary traits viz., days to maturity (DM), number of productive tillers (NPT), plant height (PH), panicle weight (PW), spikelet fertility (SF), spikelet number per panicle (SNP), and thousand seed weight (TSW) of 18 Philippine registered inbred rice were studied using different statistical parameters viz., correlation analysis, genotypic and phenotypic coefficient of variability (GCV and PCV), broad sense heritability (H2b), and genetic advance (GA). There was a significant, positive, and strong correlation between DM and PH, PW and SNP, PW and GY, and SNP and GY. GCV showed moderate variability in PW with 11.94% and NPT with 10.55%. PCV also showed moderate variability in NPT with 17.23%, GY with 14.3%, PW with 13.89% and SNP with 12.67%. All traits except for PW and SNP in GCV and traits except for NPT, GY, PW, and SNP in PCV showed low variability. H2b too had PH with 79.26%, PW with 73.91%, and SNP with 60.39% as high heritability while GA expressed to the mean (GAM) had PW with 21.14% as high genetic gain. The study found out that PW and SNP had positive and strong association to GY, but only PW had consistent and considerable amount of genotypic and phenotypic variations. Furthermore, high H2b along with high GAM was only obtained in PW. Therefore, the different statistical parameters were in congruent with the implication that higher grain yield can be achieved by attaining genotypic selection in PW. (Author's abstract)